A Morphological Stylistic Analysis of Song â€œI Wish I Hated Youâ€ by Ariana Grande - Artika, Mutiara Romi; Dalimunte, Vina Fitriani; Sofilla, Devi; Rangkuti, Rahmadsyah (LPPM Universitas Bumigora Mataram, 2024)
In societal interactions, language plays a fundamental role, serving crucial purposes. Language activities aim to express specific intentions and objectives. This study aims to examines Ariana Grande's song